Will You Forgive Your Supervisor’s Wrongdoings? The Moral Licensing Effect of Ethical Leader Behaviors - Wang, Rong; Chan, Darius K.-S. (Frontiers in Psychology, 2019)
Moral licensing theory suggests that observers may liberate actors to behave in morally questionable ways due to the actors’ history of moral behaviors. Drawing on this view, a scenario experiment with a 2 (high vs. low ethical)×2 (internal vs. external motivation) between-subject design (N = 455) was conducted in the current study. We examined whether prior ethical leader behaviors cause subordinates to license subsequent abusive supervision, as well as the moderating role of behavior motivation on such effects. The results showed that when supervisors demonstrated prior ethical behaviors, subordinates, as victims, liberated them to act in abusive ways. Specifically, subordinates showed high levels of tolerance and low levels of condemnation towards abusive supervision and seldom experienced emotional responses to supervisors’ abusive behaviors. Moreover, subordinates tended to attribute abusive supervision, viewed as a kind of mistreatment without an immediate intent to cause harm, to characteristics of the victims and of the organization rather than of the supervisors per se. When supervisors behaved morally out of internal rather than external motivations, the aforementioned licensing effects were stronger.